2009
DOI: 10.1021/la901737y
|View full text |Cite
|
Sign up to set email alerts
|

Drop Shedding by Shear Flow for Hydrophilic to Superhydrophobic Surfaces

Abstract: A balance of surface science and aerodynamic knowledge is brought to bear to elucidate the fundamental parameters determining the incipient motion (runback) for a drop exposed to shearing airflow. It was found that wetting parameters such as contact angle are very influential in determining the minimum required air velocity for drop shedding. On the basis of experimental results for drops of water and hexadecane (0.5-100 microL) on PMMA, Teflon, and a superhydrophobic aluminum surface, an exponential function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
141
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 25 publications
15
141
1
Order By: Relevance
“…Therefore, U crit for droplet roll-off/sliding on superhydrophobic surfaces was lower than for smooth, hydrophobic surfaces with lower contact angle, higher CAH and smaller frontal area (for example, surface 3 and 4 in Table 1) 15 . For suitably designed superhydrophobic surfaces, air pockets can be trapped below the water drop (Cassie state), which results in reduced CAH and less sticking 16 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, U crit for droplet roll-off/sliding on superhydrophobic surfaces was lower than for smooth, hydrophobic surfaces with lower contact angle, higher CAH and smaller frontal area (for example, surface 3 and 4 in Table 1) 15 . For suitably designed superhydrophobic surfaces, air pockets can be trapped below the water drop (Cassie state), which results in reduced CAH and less sticking 16 .…”
Section: Resultsmentioning
confidence: 93%
“…The difference between the advancing and the receding contact angles is referred to as contact angle hysteresis (CAH) 15,16 . The critical shear flow velocity, U crit , for the onset of droplet roll-off/sliding depends on factors such as the drop shape, properties and substrate wettability.…”
Section: Resultsmentioning
confidence: 99%
“…As the small deposited water droplets coalesce, the growing droplets are influenced by the competition between aerodynamic drag forces ( F drag ) and surface adhesion forces ( F adhesion ). [28][29][30] When the drag force overwhelms the adhesion force, the droplets are re-entrained in the fog flow, leading to a decrease in the fog collection efficiency (Figure 3a). …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that droplet contact time can be reduced by increasing the receding contact angle [25] or by switching recoiling dynamics from an axisymmetric retraction to a nonaxisymmetric one [23] up to about 50% (based on inertia-capillary time scale [26]: ρD 3 o /8σ 1/2 ) through breaking up the droplets and also through the pancake bouncing mechanism [27]. Although the aforementioned techniques were used to reduces droplet adhesion with a surface by minimizing droplet contact time or by shedding the droplet by airflow [16,28], the effect of stagnation air flow on an impacting water drop [29] whether in room or super cooling conditions has not been fully addressed yet. In the present study, the influence of stagnation flow on a spreading water droplet is evaluated through classical Homann flow approach [30].…”
Section: Introductionmentioning
confidence: 99%